PREPARATION OF ULTRA-DISPERSED TUNGSTEN CARBIDE POWDERS BY REMOVAL OF METHANE IN MELTS - ZALYUBOVSKYI, MARK; SMACHYLO, OKSANA; LYCHOV, DMYTRO; MIROSHYN, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
For the separation of tungsten compounds from ores and concentrates as an alternative to the method of dissolution in various acids, the method of high-temperature selective extraction (HTSE) in salt melts has been proposed. It is proved that tungsten ores and concentrates decompose at a temperature of 1050-11000C in the molten mixture of sodium chloride-sodium metasilicate, forming two immiscible phases: tungstate halide and silicate. The first contains 96-99% of tungsten, and the second - more than 90% of ore components. The high manufacturability of HTS is due to the ability of sodium tungstate to mix with sodium chloride in any ratio and the immiscibility of the silicate phase with tungstate halide. To produce tungsten, a method for the reduction of tungsten-containing melts with methane has been proposed, which is classified as a method for the reduction of oxides and other compounds by nonmetals and their compounds. The best gas for bubbling is methane. It combines directly with tungsten and the formed tungsten carbide contains a very small amount of free carbon (up to 0.03%). In the temperature range of 1050-11000C tungsten carbide yield increases to 70 percent or more. The experimentally obtained tungsten carbide contained 6.08% of bound carbon and 0.03% of free carbon. These data practically correspond to the stoichiometric composition equal to 6.13%. The distribution of ultrafine tungsten carbide powder by fractions is as follows: 0.00-0.50 μm - 25.16%; 0.50-2.00 μm - 53.29%; 2.0-5.0 μm - 100%. The main part of the grains is a double triangular prism. The gas-treated tungsten carbide is easily ground and can be obtained into any fine powder, which is important for pressing and to increase the catalytic properties of the powder. The work carried out TTS tungsten from appropriate concentrates, determined the most technological parameters of the process (temperature, melt composition, extraction duration) and developed recommendations for obtaining ultrafine tungsten carbide powders by reduction of methane in melts.
Keywords: tungsten carbide; ultrafine powders; method of high-temperature selective extraction; methane; chemical reaction